2022
DOI: 10.1186/s13073-022-01041-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in targetable genomic alterations in non-small cell lung cancer by genetic ancestry, sex, smoking history, and histology

Abstract: Background Genomic alterations in 8 genes are now the targets of FDA-approved therapeutics in non-small cell lung cancer (NSCLC), but their distribution according to genetic ancestry, sex, histology, and smoking is not well established. Methods Using multi-institutional genetic testing data from GENIE, we characterize the distribution of targetable genomic alterations in 8 genes among 8675 patients with NSCLC (discovery cohort: DFCI, N = 3115; vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Genetic ancestry level analyses conducted in Genome-Wide Association Studies (GWAS) have successfully identified differences in NSCLC risk, incidence, and survival across ancestral groups ( Zanetti et al, 2016 ; Jones et al, 2019 ; Schenk et al, 2020 ; Sinha et al, 2020 ; Adib et al, 2022 ). Sinha et al (2020) compared the frequency of copy number mutations and homologous recombination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic ancestry level analyses conducted in Genome-Wide Association Studies (GWAS) have successfully identified differences in NSCLC risk, incidence, and survival across ancestral groups ( Zanetti et al, 2016 ; Jones et al, 2019 ; Schenk et al, 2020 ; Sinha et al, 2020 ; Adib et al, 2022 ). Sinha et al (2020) compared the frequency of copy number mutations and homologous recombination.…”
Section: Resultsmentioning
confidence: 99%
“…There was no evidence of associations between any of these novel gene variants and prognosis/overall survival outcome in NSCLC. Overall, findings suggest that genetic ancestry alone is not a significant predictor of lung cancer risk, incidence, nor survival (Araujo et al, 2015b;Zanetti et al, 2016;Jones et al, 2018;Jones et al, 2019;Mitchell et al, 2019;Schenk et al, 2020;Adib et al, 2022).…”
Section: African Ancestrymentioning
confidence: 99%
“…LUAD is the accepted common classification of lung cancer, accompanied by high prevalence and fatality ( 2 , 56 ). In cancer patients, metastasis is primary cause of shorten survival and high mortality, and often has already occurred at the time of diagnosis ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges associated with capturing and analyzing self-reported race in the clinical trial setting has been well-described in the literature (72). The use of genomic ancestry in this real-world population offers a model for describing genomic differences across ancestral populations and contributes to a growing number of similar studies in other cancer types (73)(74)(75).…”
Section: Pg 15mentioning
confidence: 99%